Haskell can use normal software testing methods to verify correctness, but because haskell is a pure language, we can do better and formally prove properties of our functions and types.

## Natural Numbers

Natural numbers can be defined as data Nat = Z | S Nat in haskell. Alternatively, using mathematical notation, this can be written . Addition can then be defined recursively:

add :: Nat -> Nat -> Nat


Addition has certain properties which must hold true:

• Left identity: ∀m :: Nat, add Z m == m
• Right identity: ∀m :: Nat, add m Z == m
• Associativity: ∀x y z :: Nat, add x (add y z) == add (add x y) z

These can be proven using equational reasoning, which proves that an equality holds in all cases. Generally, either a property can be proved by applying and un-applying either side of an equation, and/or by induction.

To prove the left identity is easy, as it is an exact match of one of our equations for add:

add Z m
= m


The right identity is a little harder, as we can't just directly apply one of our equations. We can instead induct on m. First, the base case:

add Z Z
= Z


Using the induction hypothesis add m Z = m, we need to show the inductive step holds for S m (m+1):

add (S m) Z
-- applying induction hypothesis
= S m


This proves the right identity. To prove associativity we will again use induction, this time on x. The base case is add Z (add y z):

add Z (add y z)


The proof holds for x = Z. Here, the proof was approached from either end to meet in the middle, but written as a single list of operations for clarity. Sometimes it is easier to do this and work from either direction, especially when un-applying functions as it is more natural.

The induction hypothesis is add x (add y z) == add (add x y) z, and can be assumed. We need to prove the inductive step add (S x) (add y z) == add (add (S x) y) z:

add (S x) (add y z)
-- applying induction hypothesis


This proves associativity.

## Induction on Lists

We can induct on any recursive type, including lists: data List a = Empty | Cons a (List a). Using this definition, we can prove map fusion. Map fusion states that we can turn multiple consecutive map operations into a single one with composed functions:

• map f (map g xs) = map (f.g) xs
• ∀f :: b -> c
• ∀g :: a -> b
• ∀xs :: [a]

The definitions of map and . may be useful:

map :: (a -> b) -> [a] -> [b]
map f []     = []
map f (x:xs) = f x : map f xs

(.) :: (b -> c) -> (a -> b) -> a -> c
(.) f g x = f (g x)


Map fusion can be proved by induction on xs. The base case is map f (map g []) = map (f.g) []:

map f (map g [])
-- applying map
= map f []
-- applying map
= []
-- un-applying map
= map (f.g) []


Using the induction hypothesis map f (map g xs) = map (f.g) xs, we can prove the inductive case map f (map g (x : xs)) = map (f.g) (x : xs):

map f (map g (x : xs))
-- applying map
= map f (g x : map g xs)
-- applying map
= f (g x) : map f (map g xs)
-- induction hypothesis
= f (g x) : map (f.g) xs
-- un-applying (.)
= (f.g) x : map (f.g) xs
-- un-applying map
= map (f.g) (x : xs)


## Proving a Compiler

Given a simple expression language:

data Expr = Val Int | Plus Expr Expr


And a simple instruction set:

data Instr = Push Int | Add
type Program = [Instr]
type Stack = [Int]


We can write an exec function as an interpreter for our instruction set:

exec :: Program -> Stack -> Stack
exec []                    s  = s
exec (Push n : p)          s  = exec p (n : s)
exec (Add    : p) (y : x : s) = exec p (x + y : s)


An eval function to evaluate our expressions:

eval :: Expr -> Int
eval (Val n)    = n
eval (Plus l r) = eval l + eval r



And a comp function as a compiler for our Expr language to our Instr instruction set:

comp :: Expr -> Program
comp (Val n) = [PUSH n]
comp (Plus l r) = comp l ++ comp r ++ [ADD]


Our compiler will be considered correct if for any expression, evaluating it yields the same result as compiling and then executing it:

∀ e :: Expr, s :: Stack . eval e : s == exec (comp e) s


This can be proved by induction on e. The base case for Expr is for Vals, and we want to show that eval (Val n) s == exec (comp (Val n)) s. This time, we start with the RHS:

exec (comp (Val n)) s
-- applying comp
= exec [Push n] s
-- applying exec
= exec [] (n : s)
-- applying exec
= (n : s)
-- unappplying eval
= eval (Val n) s


Our inductive case to be proved is eval (Plus l r) s == exec (comp (Plus l r)) s. Since the Plus constructor has two values of type Expr, there are two induction hypotheses:

• for l: eval l : s == exec (comp l) s
• for r: eval r : s == exec (comp r) s
exec (comp (Plus l r)) s
-- applying comp
= exec (comp l ++ comp r ++ [Add]) s
-- distributivity of (++)
= exec (comp l ++ (comp r ++ [Add])) s
-- distributivity lemma
= exec (comp r ++ [Add]) (exec (comp l) s)
-- distributivity lemma
= exec [Add] (exec (comp r) (exec (comp l) s))
-- induction hypothesis
= exec [Add] (exec (comp r) (eval l : s))
-- induction hypothesis
= exec [Add] (eval r : (eval l : s))
-- applying exec
= exec [] ((eval l + eval r) : s)
-- applying exec
= (eval l + eval r) : s
-- un-applying exec
= eval (Plus l r) s


The proof holds, but relies on a lemma proving the distributivity of the exec function, which states that executing a program where a list of instructions xs is followed by a list of instructions ys is the same as first executing xs and then executing ys with the stack that results from executing xs: ∀ xs ys::Program, s::Stack . exec (xs++ys) s == exec ys (exec xs s).

This can be proved by induction on xs. The base case is the empty list []: exec ([] ++ ys) s == exec ys (exec [] s):

exec ys (exec [] s)
-- applying exec
= exec ys s
-- un-applying (++)
= exec ([] ++ ys) s


The induction hypothesis is exec (xs++ys) s == exec ys (exec xs s). The inductive step is exec ((x : xs) ++ ys) s == exec ys (exec (x : xs) s). As x could be either Push x or Add, we perform case analysis on x, first with the case where x = Push n:

exec ys (exec (Push n : xs) s)
-- applying exec
= exec ys (exec xs (n : ns))
-- induction hypothesis
= exec (xs ++ ys) (n : s)
-- un-applying exec
= exec (Push n : (xs ++ ys)) s
-- un-applying (++)
= exec ((Push n : xs) ++ ys) s


The inductive step holds for the Push n case. The Add case:

exec ys (exec (Add : xs) s)
-- assuming stack has at least 2 elements
exec ys (exec (Add : xs) (b : a : s'))
-- applying exec
exec ys (exec xs (a + b : s'))
-- induction hypothesis
exec (xs ++ ys) (a + b : s')
-- un-applying exec
exec (Add : (xs ++ ys)) (b : a : s')
-- un-applying (++)
exec ((Add : xs) ++ ys) (b : a : s')
-- assumption
exec ((Add : xs) ++ ys) s


This proves the inductive case for the Add instruction, and therefore the proof for the distributivity of exec lemma, which supported our initial proof of the correctness of our compiler.